Cultural identity dynamics: Capturing changes in cultural identities over time and their intraindividual organization. (13th February 2018) - Amiot, Catherine E.; Doucerain, Marina M.; Zhou, Biru; Ryder, Andrew G.
Abstract: Important life transitions – such as migration – have the potential to enrich one's sense of self, but they are also demanding and challenging. The current research investigates how cultural identities change and become configured over time among newly arrived international students and the social factors that predict these longitudinal changes. A four‐wave longitudinal study was conducted during international students' first year in their new country ( N  = 278). Multivariate hierarchical linear modeling analyses allowed us to unpack both baseline (between‐person) and intraindividual change (within‐person) effects. Whereas increased psychological need satisfaction via both the new and one's heritage cultural group predicted increased identity integration, greater discrimination (i.e., both at baseline and an increase over time) predicted increased compartmentalization and the predominance (categorization) of one identity over the others. Results are discussed in light of novel theoretical developments in the acculturation and identity change literatures.